Portable wind turbine - Bahari, Azlina; Subramaniam, Rutivarman A/L (Progress in Engineering Application and Technology, 2020)
Awareness about the important of renewable energy such as solar, wind and geothermal as a primary alternative to non-renewable energy sources has been increase among the world society.